Emergency department utilization by patients with gynecologic cancer in the United States. Issue 4 (April 2021) - Albright, Benjamin B; Delgado, Mucio K; Latif, Nawar A; Giuntoli, Robert L; Ko, Emily M; Haggerty, Ashley F
Abstract : Introduction : Payment reform will give oncologists increasing responsibility for how patients with cancer meet unexpected care needs. Objective : To differentiate how patients with gynecologic cancers use emergency care, and to assess the characteristics associated with potentially avoidable treat‐and‐release visits. Methods : We performed a retrospective cohort study using the Nationwide Emergency Department Sample, a stratified sample of visits in United States hospital‐based emergency departments, from 2010 to 2014. Visits by patients with a diagnosis of gynecologic cancer were selected. Sample weights were applied to calculate national estimates of care patterns and trends. Associations with treat‐and‐release disposition were assessed with weighted logistic regression. Results : In the study period, patients with gynecologic cancer made an estimated 370 104 annual emergency department visits (95% CI 351 997 to 388 211). A total of 50.2% of patients were treated and released, 48% were admitted, 1.6% were transferred, and 0.1% died. These visits corresponded to over US1.27 billion in annual charges, with an average charge of US3428 per visit (95% CI 3348 to 3509). Driven by growing treat‐and‐release utilization, annual visits increased, while admission rates fell over time. Patients with cervical cancer represented the plurality (36%) of visits; they were relatively younger, of lower socioeconomic status, and had fewer co‐morbidities. Models for treat‐and‐release disposition did not vary significantly across different cancer populations. In the all‐cancer model, increased odds of treat‐and‐release disposition was associated with cervical cancer diagnosis, younger age, lesser Elixhauser co‐morbidity, Medicare coverage (OR=1.19; p<0.001), Medicaid coverage (OR=1.25; p<0.001), uninsured status (OR=1.70; p<0.001), and weekend visits. Visits in the northeast, at urban hospitals, and in winter months showed decreased odds of treat‐and‐release disposition. Discussion : Patients with gynecologic cancers have been using the emergency department at increasing rates, primarily driven by treat‐and‐release visits that did not result in admission or death. Patients with cervical cancer have higher rates of treat‐and‐release utilization and may over‐use emergency department care.